Is it time for comprehensive geriatric assessment to move beyond primary care? The case for targeting medical sub-specialty practice - Laura K. Byerly; G. Michael Harper (BMC, 2017)
Abstract Comprehensive geriatric assessment (CGA) as a consultative service for older adults with complex medical and psychosocial challenges has existed for decades. However, studies have often showed inconsistent acceptance and implementation of geriatric recommendations by primary care providers (PCPs) raising doubts about the overall benefits of CGA in this setting. Press and colleagues investigated the patient- and provider-related factors that affect recommendation implementation, and like previous studies, they too found similarly low rates of implementation. In this commentary, we acknowledge the perennial challenges that exist to improving the acceptance of CGA in primary care practice, and we suggest an alternative target: medical sub-specialty practice. By highlighting three medical sub-specialty fields (oncology, nephrology, and cardiology), which have demonstrated that CGA can be incorporated into their respective clinical practices, we argue that CGA may prove to have greater impact in these settings than in primary care. We also propose initial research steps that could further delineate the trends, outcomes, and next steps for such consultations.